2014
DOI: 10.2147/ppa.s50583
|View full text |Cite
|
Sign up to set email alerts
|

Results of a human factors experiment of the usability and patient acceptance of a new autoinjector in patients with rheumatoid arthritis

Abstract: PurposeThis study evaluated the human factors affecting the ease of use of a disposable autoinjector developed for subcutaneous self-injections performed by patients with chronic diseases.Materials and methodsThis was a randomized, single-center study conducted with 65 patients with rheumatoid arthritis. Patients performed six simulated injections. Assessments of patient device acceptance and device usability were made by patient reports and independent observations of compliance with the device instruction fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 24 publications
2
37
0
4
Order By: Relevance
“…These results mirror those observed with another biologic agent, golimumab, when administered SC by standard needle and syringe or a similar autoinjector device to that used in the current study . The use of autoinjectors among patients with RA, including those with severe hand disability, is associated with a high level of acceptance and increased treatment compliance . Thus, data from the current pharmacokinetic study suggest the potential for switching from the existing PFS‐U presentation that was used in the phase 3 efficacy studies to the PFS‐AI device for administration of sirukumab.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…These results mirror those observed with another biologic agent, golimumab, when administered SC by standard needle and syringe or a similar autoinjector device to that used in the current study . The use of autoinjectors among patients with RA, including those with severe hand disability, is associated with a high level of acceptance and increased treatment compliance . Thus, data from the current pharmacokinetic study suggest the potential for switching from the existing PFS‐U presentation that was used in the phase 3 efficacy studies to the PFS‐AI device for administration of sirukumab.…”
Section: Discussionsupporting
confidence: 76%
“…11 The use of autoinjectors among patients with RA, including those with severe hand disability, is associated with a high level of acceptance and increased treatment compliance. 12 Thus, data from the current pharmacokinetic study suggest the potential for switching from the existing PFS-U presentation that was used in the phase 3 efficacy studies to the PFS-AI device for administration of sirukumab.…”
Section: Discussionmentioning
confidence: 95%
“…One limitation of this study was the small proportion of adolescent (7%) and older patients (!65 years, 16%) in the study population. Further information on the usability of the AI device in these populations would be beneficial; however, other studies have shown that high injection success rates were achieved with AI devices across a variety of participant demographics and disease characteristics (19)(20)(21). A further study limitation was the potential for patient selection bias given that only patients who were willing to selfadminister mepolizumab at home participated.…”
Section: Discussionmentioning
confidence: 99%
“…Altogether, the attributes of the Benepali autoinjector that patients most preferred, which were in alignment with results from the nurse survey [17], can be described as those that make the handling process easier for the patient, suggesting that both patients and nurses in Europe consider the Benepali autoinjector to be easier to handle than the Enbrel MYCLIC autoinjector. This is of paramount importance, as many patients with RA suffer from compromised dexterity, which can affect the ability to perform the steps required [20]. …”
Section: Discussionmentioning
confidence: 99%